Chapter Didattica immersiva nell'Ingegneria Agraria. Un caso d'uso nel Laboratorio di Agricoltura Digitale e di Alta Tecnologia - vieri, marco (Studi e saggi, 2022)
The chapter describes experiences of 360° videos use by the Agrismart Lab Group of the University of Florence. The Agrismart Lab Group focuses on the technological transfer of information obtained during the research phase to provide the greatest possible diffusion and dissemination of discoveries regarding the technological-digital revolution in the agricultural sector. Dissemination, applications, and teaching are the main outcomes of our research activities, and we have fully utilized the SEPA360 project's resources. In particular, the student will be able to see smart farming examples both in the field and in the immersive teaching lab having clearer theoretical notions by 360° viewers. Two case studies (tractor 4.0 and Agrobot) are included in the interactive videos, which are utilized both for learning and verification.